1991
DOI: 10.1248/cpb.39.1620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight in amphipathic polyethyleneglycol on prolonging the circulation time of large unilamellar liposomes.

Abstract: The effect in mice of the molecular weight of polyethyleneglycol on prolonging the circulation time of large unilamellar liposomes (LUVs) was examined using four different distearoyl N-(monomethoxy polyethyleneglycol succinyl) phosphatidylethanolamines (DSPE-PEGs). The molecular weights tested were 1000, 2000, 5000 and 12000. Incorporation of 6 mol% of DSPE-PEG in LUV composed of distearoylphosphatidylcholine (DSPC) / cholesterol (CH) (1:1 in molar ratio) increased the blood circulation half-life significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Chemical modifi cation of pharmaceutical nanocarriers with certain synthetic polymers, such as PEG, is the approach most frequently used to impart in vivo longevity to drug carriers, as was fi rst suggested for liposomes. [45][46][47][48][49] Hydrophilic polymers have been shown to protect individual molecules and solid particulates from interaction with different solutes. The term " steric stabilization " has been introduced to describe the phenomenon of polymermediated protection.…”
Section: Role Of Nanocarrier Longevity In the Bloodmentioning
confidence: 99%
“…Chemical modifi cation of pharmaceutical nanocarriers with certain synthetic polymers, such as PEG, is the approach most frequently used to impart in vivo longevity to drug carriers, as was fi rst suggested for liposomes. [45][46][47][48][49] Hydrophilic polymers have been shown to protect individual molecules and solid particulates from interaction with different solutes. The term " steric stabilization " has been introduced to describe the phenomenon of polymermediated protection.…”
Section: Role Of Nanocarrier Longevity In the Bloodmentioning
confidence: 99%
“…Chemical modification of pharmaceutical nanocarriers with certain synthetic polymers, such as polyethylene glycol (PEG), is the most frequent way to impart the in vivo longevity to drug carriers, as was first suggested for liposomes (17)(18)(19)(20)(21). This polymer is nontoxic, non-immunogenic, nonantigenic, highly soluble in water, and FDA approved (22).…”
Section: Introductionmentioning
confidence: 99%
“…12 For a series of PEG derivatives (MW 120-5,000 Da) used in hydrogenated soybean phosphatidylcholine (HSPC):choles terol:poly(ethylene glycol)-distearoylphosphatidylethanolamine (PEG-DSPE) liposomes with a size of 100 nm, it was reported that PEG with a molecular weight of ,750 Da promoted blood clearance and PEG with a molecular weight of .1,000 Da did not further increase the residence time of the vehicles in the blood. [12][13][14][15] Maruyama et al reported that liposomes (200 nm diameter) with PEG1000 or PEG2000 led to higher blood levels compared to liposomes with PEG5000. 16 The liposome composition, including the lipids, PEG, and PEG-lipids, is likely to influence the performance of colloidal particles in the blood and the tissue distribution.…”
Section: Introductionmentioning
confidence: 99%